Kombinasi Fermentasi Bakteri Asam Laktat dan Pemanasan Bertekanan-Pendinginan dalam Pembentukan Pati Resisten Tepung Talas Beneng (Xanthosoma undipes K. Koch) - Ilham Faozi; Karseno Karseno; Isti Handayani (Jurnal Ilmu Pertanian Indonesia, 2023)
The study aimed to determine the effect of lactic acid bacteria, fermentation time, and pressurized heating-cooling cycle on the formation of resistant starch content of beneng taro (Xanthosoma undipes K. Koch) flour. The materials used were beneng corm, isolates of lactic acid bacteria Lactobacillus casei and Streptococcus thermophilus, and MRSB media. The experimental design was randomized block design factorial with two factors: fermentation time (0, 18, and 24 hours) and pressurized-cooling heating (1, 2, and 3- cycles) in 3 replicates. The data were analyzed using analysis of variance and if necessary continued with Duncan's Multiple Range Test at a level of 95%. The tested parameters were the content of resistant starch, amylose, and amylopectin and the data were treated using variance of analysis. The results showed that the combination of L. casei and S. thermophillus produced the highest resistant starch content of 5.66%. Fermentation time of 18 and 24 hours produced resistant starch content of 4.46% and 4.51%, respectively. Autoclaving-cooling of 1-, 2-, and 3-cycle produced a similar type of resistant starch of 3.81%, 4.26%, and 4.16%, respectively. Therefore, the combination of L. casei and S. thermophillus fermented in 18 hours and 1-cycle of autoclaving-cooling is recommended to produce resistant beneng taro flour starch content. Keywords: fermentation, autoclaving-cooling, resistant starch, taro beneng, Xanthosoma undipes K. Koch